MODELING HIV/AIDS USING SHAT MODEL - Chandra, Tjang Daniel; Permata, Gloria Indah (PATTIMURA UNIVERSITY, 2023)
HIV/AIDS gets on the list of deadly infectious diseases, but there is no right medicine and vaccination for it until now. Indonesia is also inseparable from the spread of HIV/AIDS year by year number of people living with HIV/AIDS in Indonesia continues to grow. The peak of HIV cases over the last twelve years (starting from 2020) in Indonesia was 50,282 cases in 2019, then the peak of AIDS was 12,214 in 2013. The purpose of the study is to model the spread of HIV/AIDS and test it with data on the growth of HIV/AIDS in Indonesia from 2006 to 2018. The steps taken in conducting this research are to determine the equilibrium point, calculate the basic reproduction number, analyze the stability of the equilibrium point, and numeric simulation of the SHAT model with the Maple 18 tool. Numerical simulation produces a value of . Based on calculations using the Routh-Hurwitz table, we can find that the system will be asymptotically stable towards a disease-free equilibrium point, namely . Based on the results obtained, it can conclude that HIV/AIDS will not become an epidemic in Indonesia.